2007
DOI: 10.1002/jcb.21181
|View full text |Cite
|
Sign up to set email alerts
|

The immunosuppressant FTY720 inhibits tumor angiogenesis via the sphingosine 1‐phosphate receptor 1

Abstract: FTY720, a sphingosine 1-phosphate (S1P) analog, acts as an immunosuppressant through trapping of T cells in secondary lymphoid tissues. FTY720 was also shown to prevent tumor growth and to inhibit vascular permeability. The MTT proliferation assay illustrated that endothelial cells are more susceptible to the anti-proliferative effect of FTY720 than Lewis lung carcinoma (LLC1) cells. In a spheroid angiogenesis model, FTY720 potently inhibited the sprouting activity of VEGF-A-stimulated endothelial cells even a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 45 publications
(70 reference statements)
3
41
1
Order By: Relevance
“…Previous studies identify S1P as a pro-angiogenic factor (Schmid et al, 2007;Yonesu et al, 2009). By contrast, we show that S1P 1 acts to block sprouting and restrict angiogenesis.…”
Section: Research Articlecontrasting
confidence: 58%
“…Previous studies identify S1P as a pro-angiogenic factor (Schmid et al, 2007;Yonesu et al, 2009). By contrast, we show that S1P 1 acts to block sprouting and restrict angiogenesis.…”
Section: Research Articlecontrasting
confidence: 58%
“…3,27 In contrast, other studies have reported that FTY720 actually inhibits vascular endothelial growth factor-induced vascular permeability and angiogenesis. [28][29][30] The antiangiogenic effects of FTY720, though surprising based on its potent agonist activity, are proposed to occur as a result of functional antagonism. Although both S1P and FTY720 have been shown to internalize the S1P 1 receptor into the endosomal pathway, FTY720 induces ubiquitinylation and proteosomal degradation of the receptor.…”
mentioning
confidence: 99%
“…These tubules were visualised by immunostaining for MCAM, which is specifically expressed by ECs (Fig. 1B) (Schmid et al, 2007). Initially, only fibroblasts and human coronary artery ECs (no SMCs) were seeded, which similarly results in the formation of endothelial tubules.…”
Section: S1p Inhibition Of Angiogenesis In a Co-culture Model Requirementioning
confidence: 98%